2011
DOI: 10.1177/000348941112000804
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Dilation of the Frontal Recess: A Randomized Clinical Trial

Abstract: Balloon dilation of the frontal recess is a relatively safe and effective tool in the management of chronic frontal rhinosinusitis after intensive medical treatment has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 34 publications
3
66
0
2
Order By: Relevance
“…The earliest RCT compared balloon dilation of the frontal recess vs ESS and found no significant difference in outcome. 1133 A more recent study compared Draf 2a frontal sinusotomy to a "hybrid" frontal approach combining balloon dilation of the frontal recess and traditional endoscopic techniques; the study found comparable rates of ostial patency up to 1 year postoperatively, with the hybrid technique having a slightly shorter surgical time and less mean blood loss volume vs conventional ESS. 1134 A third RCT looked at maxillary sinus balloon dilation vs ESS in patients with chronic maxillary sinusitis with or without anterior ethmoid disease.…”
Section: Ixe Aecrs: Complicationsmentioning
confidence: 99%
“…The earliest RCT compared balloon dilation of the frontal recess vs ESS and found no significant difference in outcome. 1133 A more recent study compared Draf 2a frontal sinusotomy to a "hybrid" frontal approach combining balloon dilation of the frontal recess and traditional endoscopic techniques; the study found comparable rates of ostial patency up to 1 year postoperatively, with the hybrid technique having a slightly shorter surgical time and less mean blood loss volume vs conventional ESS. 1134 A third RCT looked at maxillary sinus balloon dilation vs ESS in patients with chronic maxillary sinusitis with or without anterior ethmoid disease.…”
Section: Ixe Aecrs: Complicationsmentioning
confidence: 99%
“…The disadvantages of the procedure are the lack of knowledge of its long-term effect, the high costs of the disposable instruments, and its technical limitations in ethmoidal area or in removal of atypical mucosa [9]. Several uncontrolled and controlled studies have suggested balloon sinuplasty to be a safe and effective method [6,7,[10][11][12][13]. However, the limitations of these studies are the heterogeneity of patients and procedures as well as short follow-up time, which makes the conclusions difficult to draw.…”
Section: Introductionmentioning
confidence: 99%
“…5 Since their introduction to the U.S. market in 2005, balloon sinus dilation (BSD) tools are increasingly used in endoscopic sinus surgery (ESS) and have been shown to be efficacious and safe, with evidence of successful treatment outcomes comparable with "conventional" ESS. 6,7 Surgery in office settings has proven safe and effective in various surgical specialties. 8,9 In-office procedures avoid general anesthesia complications and costs (pharmacy, anesthesiologist, postanesthesia care unit).…”
mentioning
confidence: 99%